Beyond platelet activation: dysregulated lipid metabolism in defining risk and pathophysiology of VITT - Hannah Stevens; James D. McFadyen; Natalie A. Mellett; David J. Lynn; Thy Duong; Corey Giles; Jane James; Rochelle Botten; Georgina Eden; Miriam Lynn; Paul Monagle; Peter J. Meikle; et al. (Research and Practice in Thrombosis and Haemostasis)
Background: VITT has emerged as a rare but serious adverse event linked primarily to adenoviral vector COVID-19 vaccinations, such as ChAdOx1-S (Oxford/AstraZeneca) vaccination. The syndrome is characterized by thrombosis with thrombocytopenia, elevated D-dimer, and pathologic platelet factor 4 antibodies within 42 days of vaccination. Objectives: Despite dysregulated lipid metabolism underpinning many thrombotic conditions, the role of lipid alterations in VITT remains unexplored. Here, we examined the plasma lipidome of patients with VITT and compared it with those following ChAdOx1-S vaccination and with unprovoked venous thromboembolism (VTE) to understand the role of lipids in VITT pathophysiology. Methods: This was a multicenter, prospective cohort study evaluating plasma lipidomics in newly diagnosed VITT samples, which were compared with both healthy controls following ChAdOx1-S vaccination and with unprovoked VTE. Results: Comparison with ChAdOx1-S controls reveals a distinct lipid signature in VITT, characterized by elevations in phosphatidylserine and ceramide species, alongside reductions in several plasmalogens and acylcarnitine species. Notably, similarities between VITT lipid profiles and insulin resistance phenotypes suggest potential metabolic susceptibility. While few significant associations were found between VITT and VTE, an inverse correlation with several acylcarnitine species was demonstrated. Given the known anticoagulant role of acylcarnitine species, these findings suggest a plausible mechanistic pathway elevating the thrombotic potential of VITT above that of standard VTE. Conclusion: These findings underscore the important role of lipid metabolism in VITT pathophysiology and highlight the complex interplay between lipids, coagulation, and pathologic thrombosis.